Impact on area-level physical activity following the implementation of a fitness zone in Montevideo, Uruguay (2017)
Background: The aim of the study was to measure the level of physical activity (PA) of the users of an urban park before and after the installation of 2 fitness zones (FZs) and to assess the impact of that intervention on the users' level of PA. Methods: The System for Observing Play and Recreation in Communities method was applied in the urban plaza Liber Seregni in Montevideo (Uruguay): 14 different areas were mapped and then recategorized as fitness (for PAs, including sports), green, and paved zones. Observations were made in the spring (Sep-Oct) of 2011 and 2014, before and after placing 2 FZs. Participation was analyzed by gender, year, mapped areas, and zones, and significant differences were assessed using the ?2 test. Results: In total, 7342 individuals (4091 men and 3251 women) were observed. A greater number of people with intense PA could be seen in the FZ, with significant differences between 2011 (45%) and 2014 (70%; P and lt; .05). Conclusion: This is the first longitudinal study on the impact of an intervention to increase the level of PA in public spaces in Uruguay. Higher intensity levels of PA and fewer sedentary people were observed after the installation of the FZ. © 2017 Human Kinetics, Inc.